2021
DOI: 10.2147/jaa.s306416
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Eosinophilic Asthma Endotype and Clinical Outcomes: A Real-World Observational Study

Abstract: Purpose Eosinophil count elevations are predictive of adverse outcomes in patients with asthma, yet little is known regarding longitudinal eosinophil patterns and their association with clinical outcomes. The goal of this study was to assess associations between longitudinal persistence of eosinophil elevations and both clinical outcomes and health care resource utilization (HCRU). Methods Data were extracted from 2 databases in the United Kingdom. Patients included wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Consistent with evidence that eosinophilic asthma is the most common asthma phenotype, the high percentages of patients who achieved C 2 composite remission criteria also reflects that many patients enrolled in benralizumab trials have an eosinophilic component underlying their asthma; indeed, in these patients, using benralizumab as a precision approach to directly target, and almost entirely deplete, eosinophils led to clinically meaningful improvements. Patients with eosinophilic asthma or a history of elevated bEOS levels are more likely to experience asthma exacerbations or have worse lung function [6,9,45]. Exacerbations represent a substantial source of morbidity and mortality for patients with severe asthma, and they are also associated with considerable economic burden as well as a progressive decline in lung function [12,13,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with evidence that eosinophilic asthma is the most common asthma phenotype, the high percentages of patients who achieved C 2 composite remission criteria also reflects that many patients enrolled in benralizumab trials have an eosinophilic component underlying their asthma; indeed, in these patients, using benralizumab as a precision approach to directly target, and almost entirely deplete, eosinophils led to clinically meaningful improvements. Patients with eosinophilic asthma or a history of elevated bEOS levels are more likely to experience asthma exacerbations or have worse lung function [6,9,45]. Exacerbations represent a substantial source of morbidity and mortality for patients with severe asthma, and they are also associated with considerable economic burden as well as a progressive decline in lung function [12,13,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, various studies have found that an elevated eosinophil count is associated with severe asthma [ 9 , 35 – 37 , 54 , 55 ]. This is due to the fact that inflammation is firmly related to the existence of elevated eosinophils in the airway as well as the expression of the Th2 cytokine during allergic asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma endotypes can be largely classified as type 2 (T2) high or T2-low [7]. T2-high asthma is distinguished by fractional exhaled nitric oxide (FeNO) > 25 ppb, blood and airway eosinophilia (peripheral blood eosinophil levels > 300 or > 150 cells/µL, and sputum eosinophils > 2%), increased severity, and therapeutic responsiveness to Glucocorticoids and T2 inflammatory inhibitors [8,9]. During exposure to allergens, T2 inflammation coexists with eosinophilic inflammation mediated by cytokines such as interleukin (IL) -4, IL-5, and IL-13 [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of asthmatic patients have shown that persistence of eosinophils predisposes these patients to increase the risk of severe asthma exacerbations. [ 31 ] Therefore, it is best that we target these particular phenotypes with available modalities. The benefits of use of these biologicals are better asthma control, decreased exacerbation frequency, hospitalisation, reduction in steroid use, improvement in lung functions, and overall quality of life, and this has already been shown by various meta-analyses.…”
Section: Discussionmentioning
confidence: 99%